Regulation of Human Leukocyte Beta Receptors by Endogenous Catecholamines: RELATIONSHIP OF LEUKOCYTE BETA RECEPTOR DENSITY TO THE CARDIAC SENSITIVITY TO ISOPROTERENOL - Fraser, J. (1981)
High levels of beta receptor agonist have previously been shown to down-regulate beta receptor density on circulating leukocytes in man; however, the factors controlling receptor density under physiological conditions have not previously been defined. To determine whether beta receptor density is normally down-regulated by circulating, physiological levels of catecholamines we have examined the relationship between receptor density and catecholamine levels. Urinary epinephrine and norepinephrine were significantly reciprocally correlated to lymphocyte receptor density. A similar relationship existed between beta receptor density and supine plasma epinephrine, norepinephrine, upright epinephrine, and norepinephrine levels. Change in sodium intake from 10 to 400 meq/d caused a 52% increase in lymphocyte and a 48% increase in polymorphonuclear beta receptor density. The changes in receptor density were accompanied by an increase in the sensitivity to isoproterenol measured as a fall in the dose of isoproterenol required to raise the heart rate by 25 beats per minute. Beta receptor density on both lymphocyte and polymorphonuclear cells was significantly correlated to the cardiac sensitivity to isoproterenol. Propranolol administration resulted in an increase in the density of beta receptors on lymphocyte and polymorphonuclear cells that correlated with the subject's pretreatment catecholamine levels. These findings, therefore, suggest that physiological levels of catecholamines normally down-regulate beta receptors in man and that blockade of this down-regulation by propranolol allows receptor density to increase.